Chemical oxidation of m-Phenylenediamine by electro-fenton process - Panopio, Laarni V. (2006)
This study investigated the feasibility of applying electro-Fenton (EF) process in the chemical oxidation of m-phenylenediamine (m-PD). The effect of varying initial H2O2 and Fe2+ dosages, electric current, initial pH and reactant feeding mode on the efficiency of EF was assessed. The degradation behavior of m-PD was also compared with the degradation behavior of aniline, its parent compound. Results show m-PD was very rapidly oxidized by EF process. An initial dosagae of 43.6 mM H2O2 and 0.27 mM Fe2+ at 4A and initial pH of 3.2 was sufficient to achieve 100% m-PD degradation for 10 mM and m-PD solution. Increasing the initial H2O2 concentration from 14.5 to 58.1 mM enhanced the m-PD and COD removal but decreased the H2O2 efficiency. Increasing the initial Fe2+ dosage improved both the m-PD and COD removal as high as 77.8% and 23.5%, respectively, as well as increased the H2O2 efficiency. However, m-PD and COD removal decreased at 1.07 mM initial Fe2+ dosage. Increasing the applied electric current from 0 to 4A improved the m-PD removal from 54.1% to 77.1% and COD removal from 9.77% to 23.5% but further increase to 6A reduced the removal efficiencies. Based on this, EF process proved to be more superior compared to conventional Fenton (CF) process. The optimum pH for m-PD oxidation was observed to be pH 3.2 m-Phenylenediamine degraded faster an dmore easily compared to aniline but COD removal from m-PD was lower by 24.9%. An initial dosage of 581 mM H2O2 and 10.7mM Fe2+ was used to remove the COD of 40 mM m-PD solution using EF process operated at pH 3.2 and 4A. About 75.8% COD was removed and 7,800 mg/L oxalic acid was detected when 1-step H2o2 addition was employed. No benefit was gained when multi-step H2o2 addition, and multi-step Fe2+ addition were used to remove the COD but oxalic acid concentration was highest at 9,340mg/L under this condition. Aromatic ring-cleavage products including oxalic acid seem to be the main components of the residual solution. A reaction pathway for m-PD degradation was proposed based on the detected intermediates and results from previous related studies. Furthermore, the operating cost of EF process was calculated to be 35.7% cheaper than CF process. Thus, EF process is technically and economically feasible making it a viable alternative in treating wastewaters containing m-PD.